PENERAPAN KONSEP COMMUNITY BASED CORRECTION DALAM PROGRAM PEMBINAAN GUNA MEMENUHI HAK NARAPIDANA DI LEMBAGA PEMASYARAKATAN - Galih Zhoohiru; Mitro Subroto (Universitas Halu Oleo, 2022)
The concept of Community Based Correction (CBC) is an alternative in fulfilling the rights of prisoners who are in prison, by providing new opportunities for prisoners to be able to return to the community, the role of coaching also determines the success of this program, with prisoners following the coaching program well, it will make it easier for prisoners to receive their rights in prisons, the role and participation of the community in receiving prisoner coaching has a major role in the reintegration of prisoners into society. This research uses descriptive research with literature study (Library Research). Descriptive research is carried out by means of surveys, literature, and so on. This study uses a literature study that aims to explain the concept of CBC and the guidance obtained by inmates at the Correctional Institution, especially on the guidance and services provided to fulfill the rights of prisoners. The results of the study show that most open prisons have succeeded in integrating prisoners in the context of coaching with the CBC concept as an embodiment of the goals of the Correctional system.